Effects of acute waterborne exposure to harmful algal toxin domoic acid on foraging and swimming behaviours of fish early stages - Mincarelli, Luana Fiorella (2020)
Domoic acid (DA) is a neurotoxin naturally produced by Pseudo-nitzschia diatoms that may be transferred through the marine food web and cause mass mortality events at higher trophic levels. Yet, the effects of the dissolved marine toxin on foraging responses and swimming performances of fish early stages are poorly known. Here we evaluated the effects of short-term exposure (24 h) to a single dose of domoic acid (136 μg DA L-1) on larvae (15-20 days post-hatch) of three commercially important fish species (the sea breams Diplodus sargus and Sparus aurata and the meagre Argyrosomus regius). Although DA exposure did not elicit significant effects on larval survival (p > 0.05) and swimming performance (p > 0.05), the toxin significantly affected the fish capture success (p < 0.001). Our findings suggest that toxigenic Pseudo-nitzschia blooms may compromise fish early stages, in particular larvae feeding behaviours, leading to complications in the development and increasing fish vulnerability and mortality.